A RECORD OF NATURAL PEARL OYSTER PTERIA BREVILATA (DUNKER, 1873) (FAMILY: PTERIIDAE) WITH NATURAL PEARL FROM KAYALPATTINAM COAST OF GULF OF MANNAR, SOUTH EAST COAST OF INDIA - T. Vaitheeswaran; N. Jayakumar; V.K. Venkataramani (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The natural pearl oyster of Pteria brevilata species was recorded for the first time from Kayalpattinam coast of Gulf of Mannar. A specimen with pearls was collected as an incidental by-catch in the trawl fisheries, from the Kayalpattinam coast of Gulf of Mannar, South east coast of India between 08º 33’ 41.73" N lat. 78º 07’ 55.54" E long and 08º 33’ 41.28" N lat. 78º 07’ 55.58" at a depth of 10-15m.